PAPAN LOMPAT KELINCI SEBAGAI MEDIA MENGEMBANGKAN KEMAMPUAN MEMAHAMI KONSEP ANGKA 10-20 PADA ANAK USIA 5-6 TAHUN DI TK LABSCHOOL UMC - CUCU SOPIAH (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2018)
Problems in this study there are still some children aged 5-6 years in UMC Lab school Kindergarten, experiencing confusion in understanding the concept of numbers 10-20, some children can not mention the symbol of the numbers 10-20 of the largest and the smallest in sequence, and can not mention the number 10-20 symbol with the number of objects randomly. The goal is to improve the ability to recognize the concept of numbers 10-20 in UMC Lab school Kindergarten. Preliminary observations obtained data ability to recognize the concept of numbers 10-20 in children Group B Kindergarten Lab school UMC reaches 20% BSH value. Cycle I is given action with rabbit jump board media, so the ability to understand the concept of 10-20 can increase with the acquisition of 25% BSH value. The second cycle is 80% BSH and 3% BSB. At the end of the third cycle there was a significant increase of 77% BSH value and 8% BSB value. So the average success rate of Group B Labschool UMC Kindergarten students in the ability to recognize the concept of numbers 10-20 is very satisfactory.